ANALYTICAL METHOD FOR THE IDENTIFICATION OF OIL SPILL DISPERSANT COMPOSITION - M. Mulyono; R. Desrina; E. Jasjfi (Scientific Contributions Oil and Gas, 2000)
Chemical dispersants are often used to disperse spilled oils, which threaten to pollute shoreline areas. In Indonesia all dispersants produced or marketed should undergo the toxicity test with regand to certain types of fish to determine the threshold limit, LC-50. The type of surface-active agent (surfactants) and the solvent used in the dispersants, which determine the dispersing quality, might be toxic to the marine species and bacteria.